2011
DOI: 10.1080/09712119.2011.605319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-mannanase-based enzyme in corn-soy and corn-soy-canola diets on broiler performance

Abstract: A 2) 2 factorial experiment was conducted to evaluate the effects of dietary partial replacement of soybean meal (SBM) by canola meal (CM) with and without a b-mannanase-based enzyme on growth performance of broilers. A total number of 360 one-day-old broiler chicks were weighed and allocated to four iso-caloric and iso-nitrogenous diets, each of which had 9 pens of 10 chicks with the same number of both sexes. Starter, grower and finisher diets were offered to birds from 0 to 21 day, 22 to 42 day and 43 to 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In addition, this result is in agreement with previous studies on poultry (Chegeni, Torki, & Kamyab, 2011; Cho & Kim, 2013; Li, Chen, Chen, Li, & Cao, 2010) and pigs (Pettey, Carter, Senne, & Shriver, 2002). The authors attributed these results to the dietary supplementation of ß‐mannanase that decreased viscosity and improved nutrient utilization in ß‐mannans‐containing diets (Daskiran et al, 2004; Lee, Bailey, & Cartwright, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, this result is in agreement with previous studies on poultry (Chegeni, Torki, & Kamyab, 2011; Cho & Kim, 2013; Li, Chen, Chen, Li, & Cao, 2010) and pigs (Pettey, Carter, Senne, & Shriver, 2002). The authors attributed these results to the dietary supplementation of ß‐mannanase that decreased viscosity and improved nutrient utilization in ß‐mannans‐containing diets (Daskiran et al, 2004; Lee, Bailey, & Cartwright, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Chegeni et al . () reported that growth performance of broiler chickens fed canola seed was improved in cases of supplement with β‐mannanase, which belongs to the hemicellulases and functions in degrading NSP. Since A. awamori was known to produce β‐mannanase (Kurakake & Komaki ), it was hypothesized that feeding of A. awamori and canola seed have positive effects on growth performance of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…However, utilization of canola seeds as feed ingredients is often limited because of its high content of non-starch polysaccharides (NSP) (Meng et al 2005), while broiler chickens fed a diet with canola seed showed higher feed efficiency compared with chickens fed a control diet (Talebali & Farzinpour 2005). Recently, Chegeni et al (2011) reported that growth performance of broiler chickens fed canola seed was improved in cases of supplement with β-mannanase, which belongs to the hemicellulases and functions in degrading NSP. Since A. awamori was known to produce β-mannanase (Kurakake & Komaki 2001), it was hypothesized that feeding of A. awamori and canola seed have positive effects on growth performance of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%